Computational and NMR Conformational Analysis of Galactofuranoside Cycles Presented in Bacterial and Fungal Polysaccharide Antigens - Gerbst, Alexey G.; Krylov, Vadim B.; Nifantiev, Nikolay E. (Frontiers in Molecular Biosciences, 2021)
Unlike pyranoside cycles which are generally characterized with strictly defined conformational preferences, furanosides are flexible and may adopt a wide range of available conformations. During our previous studies conformational changes of galactofuranoside cycles upon total sulfation were described computationally using simple Hartree-Fock (HF) method and principal conformers of the 5-membered galactose ring were revealed. However, in case of more complex disaccharide structures it was found that this method, as well as the widely applied DFT-B3LYP, produced results that deviated from experimental evidences. In this paper other DFT functionals (PBE0 and double hybrid B2PLYP) along with RI-MP2 are employed to study the conformational behavior of the galactofuranoside ring. Reinvestigation of galactofuranosides with lactic acid substituent at O-3 revealed that changes in orientation of lactic acid residue at O-3 might induce conformational changes of furanoside cycle. Such findings are important for further modelling of carbohydrate-protein interaction.